Employing creativity skills in the delivery of academic content: focus on effective teaching and evaluation for sustainable development in the third world nations (2014)
It has been observed that students' attitude to academic work has declined in recent time and consequently, mass failure in public examinations has been on the increase. The problem has been attributed to various reasons, of which the delivery of academic content to students is the most prominent. It is therefore imperative that more modern teaching strategies be adopted for the delivery of academic content. This study, therefore, examined the current trend in teaching and learning which is still filled with a lot of lapses and advocated for the employment of creativity skills which involves a lot of activities rather than passivity in the delivery of academic content in the nation's secondary schools. The concept and application of creativity to teaching and learning process were exemplified, and highlighted. The fact that the whole process would be incomplete without the teacher's continuous personal evaluation of his own teaching for effectiveness was also stressed. It was recommended that this process should be advocated for global practice for effective delivery of academic content by all teachers which should be the tenet of the emerging trends in Learning, Education and Teaching for sustainable development and Human capacity building in the third world nations